Paternal Alcohol Exposure Reduces Alcohol Drinking and Increases Behavioral Sensitivity to Alcohol Selectively in Male Offspring - Finegersh, Andrey; Homanics, Gregg E. (PLOS ONE, 2014)
Alcohol use disorder (AUD) is heritable, but the genetic basis for this disease remains poorly understood. Although numerous gene variants have been associated with AUD, these variants account for only a small fraction of the total risk. The idea of inheritance of acquired characteristics, i.e. “epigenetic inheritance,” is re-emerging as a proven adjunct to traditional modes of genetic inheritance. We hypothesized that alcohol drinking and neurobiological sensitivity to alcohol are influenced by ancestral alcohol exposure. To test this hypothesis, we exposed male mice to chronic vapor ethanol or control conditions, mated them to ethanol-naïve females, and tested adult offspring for ethanol drinking, ethanol-induced behaviors, gene expression, and DNA methylation. We found that ethanol-sired male offspring had reduced ethanol preference and consumption, enhanced sensitivity to the anxiolytic and motor-enhancing effects of ethanol, and increased Bdnf expression in the ventral tegmental area (VTA) compared to control-sired male offspring. There were no differences among ethanol- and control-sired female offspring on these assays. Ethanol exposure also decreased DNA methylation at the BdnfÆpromoter of sire's germ cells and hypomethylation was maintained in the VTA of both male and female ethanol-sired offspring. Our findings show that paternal alcohol exposure is a previously unrecognized regulator of alcohol drinking and behavioral sensitivity to alcohol in male, but not female, offspring. Paternal alcohol exposure also induces epigenetic alterations (DNA hypomethylation) and gene expression changes that persist in the VTA of offspring. These results provide new insight into the inheritance and development of alcohol drinking behaviors.